Tinea nigra in Peru - Aguilar Celi, Polinestor (1952)
Manson in 1872, in Southern China, observed this disease, but their observations were forgotten until Castellani described the disease in 1905 and studied again calling Cladosporium Mansoni causal agent. In 1891, in Brazil Cerqueira relates several instances of "one dermatomicosis which appears as black spots located on the palms of the hands." In 1921, Ramos and Silva in Rio de Janeiro, reported another case in which Parreiras Horta isolated the fungus and classified as Cladosporium Wernecki.